LEXICAL COHESION IN BACKGROUND OF RESEARCH USED IN UNDERGRADUATE THESIS: A CASE STUDY IN MADAKO UNIVERSITY - Jaya Jaya; Hasia Marto (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
This research is aimed to get a detailed description and analysis about the representation of lexical cohesion in the background of research in undergraduate thesis from English Language Education students at Madako University. The researchers employed quantitative model to analyze the frequency and percentage of lexical cohesion which is used by the students in their writing. The data in this research were obtained from English Language Education undergraduate thesis of students at Madako University. The data collection which is used by the researchers is note taking. The data of this research were analyzed by using categorization of cohesion namely lexical cohesion. The result of this research indicates that the repetition component becomes the most dominant from the three components; the percentage of repetition is 93%, followed by synonym, collocation and superordinate with their percentage 4%, 2%, and 1% respectively.